Republic of Madagascar : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2007)
The staff report for the First Review Under the Three-Year Arrangement for the Republic of Madagascar reviews economic and financial policies. The 2007 economic program is designed to sustain growth, promote fiscal consolidation, and reduce poverty while keeping inflation to single digits and reducing the economy's vulnerability to shocks. Central bank interventions will be limited to smoothing large variations in the exchange rate and meeting the program's foreign reserve target. Planned spending reductions should offset any shortfall in revenues, which would allow the domestic financing target to be met.